Model Penanggulangan Terorisme di Indonesia: Studi Kasus Efektifitas Sinergitas Militer dan Kepolisian di Poso tahun 2016 - Kartomo, Agus; Runturambi, Arthur Josias Simon (Jurnal Kajian Stratejik Ketahanan Nasional, 2020)
Counter-terrorism is responsibility among citizen in the “Sishankamrata” doctrine. The police and military are the main elements in “Sishankamrata”. The first purpose of this study is to analyze how best practiced democratic countries to deal with terrorism, the second goal is to test how effective the synergy of the police and military in counter-terrorism. Operation Tinombala is as a case study which law enforcement operation against terrorism in Poso in 2016. This research uses qualitative methods and primary data collected from interviews to Tinombala’s members, secondary data is collected from books and open source news. The results showed that in a democratic country prioritizing a law enforcement approach in counter-terrorism and the military helps to law enforcement forces. Military assistance is carried out by training or assisting special military units to law enforcement authorities. While in the case study of Operation Tinombala in Poso in 2016, it can be concluded that police and military synergy proved effective in counter terrorism efforts. The synergy of the police and military in counter terrorism can be used as a reference in the use of a combination of legal approach and war approach in counter-terrorism efforts in Indonesia